Discourses Shaping Primary School Leaders' Approaches to Transition to School in New Zealand - Souness, Katherine; McChesney, Katrina; Kamenarac, Olivera (International Journal of Educational and Life Transitions, 2023)
Children’s initial transition from early childhood education (ECE) to school has been well studied across the world, with diverse accounts of policy and practice in a variety of contexts. However, to date, the specific contributions of those school staff in leadership roles who shape and oversee transition-to-school processes have been under-researched. Furthermore, little research to date has considered transition to school through a discourse lens. This paper responds to these gaps, reporting findings from a post-structural discourse analysis of interviews with five primary school leaders (deputy/associate principals or across school leaders) responsible for supporting children transitioning from ECE to large New Zealand primary schools. The data analysis suggested that leaders’ ways of talking about transition to school reflected four specific discourses, which we termed structural, relational, pedagogical, and achievement discourses. These discourses within the schools intersected with each other and with wider social and educational discourses (e.g., discourses of managerial leadership, “best transition practice,” sociocultural, child readiness, neoliberal, data, and play). The paper looks critically at the discourses on transition that both produce and are reproduced by policies and practices in some of New Zealand’s schools. In doing so, the paper offers a fresh perspective on the role of primary school leaders in constructing transition-to-school approaches within their school contexts. The paper highlights the importance of critical examination of discursive forces and invites school leaders and others to exercise agency in constructing transition-to-school approaches and discourses within their specific contexts.
Keywords: Transition to school; school leaders; educational leadership; discourse analysis; poststructuralism; New Zealand